2017
DOI: 10.1093/femsre/fux003
|View full text |Cite
|
Sign up to set email alerts
|

From Nano to Micro: using nanotechnology to combat microorganisms and their multidrug resistance

Abstract: The spread of antibiotic resistance and increasing prevalence of biofilm-associated infections is driving demand for new means to treat bacterial infection. Nanotechnology provides an innovative platform for addressing this challenge, with potential to manage even infections involving multidrug-resistant (MDR) bacteria. The current review summarizes recent progress over the last 2 years in the field of antibacterial nanodrugs, and describes their unique properties, mode of action and activity against MDR bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
130
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(133 citation statements)
references
References 259 publications
2
130
0
1
Order By: Relevance
“…In conclusion, factors that are likely to concur in influencing the antimicrobial potential of biogenic metal/metalloid nanoparticles can be summarized as follows: (i) the nature of constitutive elements (Natan and Banin, 2017); (ii) the size (Lu et al ., 2013; Zonaro et al ., 2015) and (iii) the surface architecture (Verma and Stellacci, 2010). Much is still to be clarified, however, in order to elucidate in detail the nature of the external organic coating of biogenic metal nanoparticles for an actual interpretation of the intimate biocidal mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, factors that are likely to concur in influencing the antimicrobial potential of biogenic metal/metalloid nanoparticles can be summarized as follows: (i) the nature of constitutive elements (Natan and Banin, 2017); (ii) the size (Lu et al ., 2013; Zonaro et al ., 2015) and (iii) the surface architecture (Verma and Stellacci, 2010). Much is still to be clarified, however, in order to elucidate in detail the nature of the external organic coating of biogenic metal nanoparticles for an actual interpretation of the intimate biocidal mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both inorganic and organic nanoparticles can be combined or modified by adding molecules (hybrid nanoparticles) to enhance their biological properties or provide multifunctionality. As excellent in-depth reviews on the principles and current applications of nanoparticles, particularly silver, are available 13,135 , we focus on clinically used liposomal nanoparticles for drug delivery and emerging technologies, including stimuli-triggered activation, that have shown efficacy in vivo .…”
Section: The Promise Of New Technologiesmentioning
confidence: 99%
“…[6][7][8] Consequently, it is highly urgent to develop novel antibiotics against various life threatening bacterial pathogens. [13][14][15][16][17][18][19] Among the variety of engineered nanoparticles that have been used in antibacterial treatments, [13,[20][21][22] AgNP is the most widely explored antibacterial nanoagent due to its broad-spectrum antimicrobial properties and robust antimicrobial effectiveness AgNPs against two types of Gram-negative bacteria, E. coli and Pseudomonas aeruginosa (P. aeruginosa). The antibacterial action of the engineered NPs is generally involved with the surface-binding of the NPs to the bacteria, ion release, followed by the generation of high oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it becomes really difficult for bacterial cells to develop multiple simultaneous gene mutations to against NP-mediated treatments. [13][14][15][16][17][18][19] Among the variety of engineered nanoparticles that have been used in antibacterial treatments, [13,[20][21][22] AgNP is the most widely explored antibacterial nanoagent due to its broad-spectrum antimicrobial properties and robust antimicrobial effectiveness AgNPs against two types of Gram-negative bacteria, E. coli and Pseudomonas aeruginosa (P. aeruginosa). [43] The results showed that upon treatment with AgNPs, the surface charge of the bacteria moved toward neutral from −28.5 ± 2.9 to −3.5 ± 0.8 mV for E. coli, and from −20.6 ± 1.8 to −5.4 ± 0.5 mV for P. aeruginosa.…”
Section: Introductionmentioning
confidence: 99%